2013
DOI: 10.1080/03079457.2013.776665
|View full text |Cite
|
Sign up to set email alerts
|

Extra-intestinal coccidiosis in the kiwi (Apteryxspp.)

Abstract: Despite significant conservation intervention, the kiwi (Apteryx spp.) is in serious population decline. To increase survival in the wild, conservation management includes rearing of young birds in captivity, safe from introduced mammalian predators. However, an increase in density of immunologically naïve kiwi increases the risk of exposure to disease, including coccidia. Intestinal coccidiosis has recently been described in the kiwi, and although extra-intestinal coccidiosis was first recognized in kiwi in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Brown Kiwi is a flightless bird endemic to New Zealand and is one of five species of kiwi classified as threatened with extinction . A New Zealand conservation management program based on rearing chicks in controlled environments has increased their chance of survival to adulthood to 65% compared to less than 5% in kiwi from unmanaged wild populations.In a recent study involving 406 kiwi chicks raised in captivity, 4.3% of them presented with retained or infected yolk sacs .…”
Section: Discussionmentioning
confidence: 99%
“…The Brown Kiwi is a flightless bird endemic to New Zealand and is one of five species of kiwi classified as threatened with extinction . A New Zealand conservation management program based on rearing chicks in controlled environments has increased their chance of survival to adulthood to 65% compared to less than 5% in kiwi from unmanaged wild populations.In a recent study involving 406 kiwi chicks raised in captivity, 4.3% of them presented with retained or infected yolk sacs .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, asexual stages of unknown coccidial species have been found in the liver, spleen, lung, and pancreas. Periodic acid Schiff staining of kidney to enhance parasite recognition is recommended as part of routine histopathologic examination (Morgan et al, 2013). Eimeriosis has also been described in red-winged tinamous.…”
Section: Protozoamentioning
confidence: 99%
“…Unfortunately, due to a build-up of environmentally resilient Eimeria spp. oocysts (Apicomplexa: Eimeriidae, Schneider 1875) and increased density of immunologically naïve hosts in Operation Nest Egg (ONE) facilities, the juvenile brown kiwi suffer morbidity and mortality delaying the programme’s ability to release kiwi into the wild (Williams, 2001 ; Yabsley, 2008 ; Morgan et al, 2012 ; Morgan et al, 2013 ). Although, coccidia infections of kiwi were first reported in the 1970s, in-depth, morphological descriptions of oocysts and endogenous stages were not described until more recently.…”
Section: Introductionmentioning
confidence: 99%
“…Morgan et al ( 2017 ) provided descriptions of four species ( Eimeria mantellii , E. kiwii , E. paraurii , E. apteryxii ) from sporulated oocysts shed by six captive brown kiwi from two ONE sites. Other reports of coccidia in kiwi include four unsporulated morphotypes described by Thompson and Wright ( 1978 ); three morphologically distinct gametocytes found in the intestinal tract (Morgan et al, 2012 ); one gametocyte reported in the renal system; and meronts in multiple visceral organs (Morgan et al, 2013 ). These reports likely overlap, describing stages of the same morphotype; however, these connections require further verification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation